RNase A Treatment Interferes With Leukocyte Recruitment, Neutrophil Extracellular Trap Formation, and Angiogenesis in Ischemic Muscle Tissue - Lasch, Manuel; Kumaraswami, Konda; Nasiscionyte, Simona; Kircher, Susanna; van den Heuvel, Dominic; Meister, Sarah; Ishikawa-Ankerhold, Hellen; Deindl, Elisabeth (Frontiers in Physiology, 2020)
Background: RNase A (the bovine equivalent to human RNase 1) and RNase 5 (angiogenin), are two closely related ribonucleases. RNase 5 is described as a powerful angiogenic factor. Whether RNase A shares the same angiogenic characteristic, or interferes with vessel growth as demonstrated for arteriogenesis, has never been investigated and is the topic of this present study. Methods and Results: To investigate whether RNase A shows a pro- or anti-angiogenic effect, we employed a murine hindlimb model, in which femoral artery ligation (FAL) results in arteriogenesis in the upper leg, and, due to provoked ischemia, in angiogenesis in the lower leg. C57BL/6J male mice underwent unilateral FAL, whereas the contralateral leg was sham operated. Two and seven days after the surgery and intravenous injection of RNase A (50 µg/kg dissolved in saline) or saline (control), the gastrocnemius muscles of mice were isolated from the lower legs for (immuno-)histological analyses. Hematoxylin and Eosin staining evidenced that RNase A treatment resulted in a higher degree of ischemic tissue damage. This was, however, associated with reduced angiogenesis, as evidenced by a reduced capillary/muscle fiber ratio. Moreover, RNase A treatment was associated with a significant reduction in leukocyte infiltration as shown by CD45+ (pan-leukocyte marker), Ly6G+ or MPO+ (neutrophils), MPO+/CitH3+ (neutrophil extracellular traps, NETs) and CD68+ (macrophages) staining. CD68/MRC1 double staining revealed that RNase A treated mice showed a reduced percentage of M1-like polarized (CD68+/MRC1-) macrophages whereas the percentage of M2-like polarized (CD68+/MRC1+) macrophages was increased. Conclusion: In contrast to RNase 5, RNase A interferes with angiogenesis, which is linked to reduced leukocyte infiltration and NETs formation.